Maternal depression and foetal responses to novel stimuli: insights from a socio-economically disadvantaged Indian cohort. (11th March 2014) - Fernandes, M.; Stein, A.; Srinivasan, K.; Menezes, G.; Renton, M.; Zani, J.; Ramchandani, P. G.
<x content-type="archive" xml:space="preserve">Abstract</x> Maternal stress during pregnancy has pervasive effects on stress responsivity in children. This study is the first to test the hypothesis that maternal prenatal depression, as observed in South India, may be associated with how foetuses respond to a potentially stressful stimulus. We employed measures of foetal heart rate at baseline, during exposure to a vibroacoustic stimulus, and post-stimulation, to study patterns of response and recovery in 133 third trimester foetuses of depressed and non-depressed mothers. We show that the association between maternal depression and foetal stress responsivity is U-shaped with foetuses of mothers with high and low depression scores demonstrating elevated responses, and poorer recovery, than foetuses of mothers with moderate levels. The right amount of intra-uterine stimulation is important in conditioning foetuses towards optimal regulation of their stress response. Our results imply that, in certain environmental contexts, exposure to moderate amounts of intra-uterine stress may facilitate this process.